Why does Hospital Social Media Marketing Public Relations Fail? A Close Observation of Brand X in Socializing its MRI Service Benefits - Reghina Elgusia (Graduate School of Communication Universitas Bakrie, 2023)
A marketing public relations (MPR) program significantly contributes to service sales, including hospitals. However, the MPR communication carried out by brand X through social media in promoting the benefits of MRI services did not impact new customer acquisition. Sales results show contributions not from social media but from direct sales to potential customers. Why did the X hospital brand MPR program fail? What's wrong? This article investigates the phenomenon of MPR program failure through digital observation methods that are inherent and close to knowing what communicative factors cause program failure. The study also interviewed vital informants behind the program and triangulated them with consumer audiences, especially followers of brand X's social media accounts. This study is essential as a lesson for other brands in implementing effective MPR programs.